A Serra dos Órgãos como barreira biogeográfica para peixes dos gêneros Astyanax Baird e Girard (1854) e Deuterodon Eigenmann (1907) (Teleostei : Characiformes : Characidae) - Melo, Filipe Augusto Gonçalves de (2000)
The species from the genera Astyanax Baird and Girard (1854) and Deuterodon Eigenmann (1907) distributed in the region of Serra dos Órgãos, part of Serra do Mar in the State of Rio de Janeiro, are reviewd. Astyanax giton Eigenmann (1908), A. hastatus Meyers (1928), A. janeiroensis Eigenmann (1908) are A. taeniatus (Jenyns, 1842) are redescribed. Astyanax fasciatus parahybae Eigenmann, (1908) are A. scabripinnis intermedius Eigenmann (1908) are elevated to species category. Astyanax parahybae differs from Astyanax fasciatus (Cuvier) species complex by the presence of scales irregulary arranged above of anal fin. Astyanax intermedius differs from A. scabripinnis (Jenyns, 1842) by the shape of dentary teeth, which heigh variates abruptally from the fifth tooth. Dentary tooth heigh from A. scabripinnis variates abuptly from the fourth teeth. Astyanax giton, A. intermedius and A. parahybae have their lectotypes designed. Two new species from Astyanax are described The first one (sp. l) belongs to species complex with ovate umeral spot, without maxilar thoot. The other (sp. 2) belongs to Astyanax fasciatus (Cuvier) species complex. Two new Deuterodon species are described. The endemicity pattern of A. intermedius, Astyanax sp. 2 sp. n. and two new Deuterodon species suggestes that the Serra dos Órgãos, which separetes coastal form Paraiba do Sul river drainages, acts such like a biogeografic barrier for that species. Astyanax hastatus, A. giton, A. taeniatus and Astyanax sp. 1 occur in the coastal and in the Paraíba do Sul river drainages from the Serra dos Órgãos.